Arduino-based automatic cutting tool for coconut shell charcoal briquettes - Anis, samsudin; Fitriyana, Deni Fajar; Anam, Fajar Chairul; Firmansyah, Hendrix Noviyanto; Bahatmaka, Aldias; Kusumastuti, Adhi; Manalu, Janviter; Siregar, Januar Parlaungan; Cionita, Tezara; Ahmad Jazilussurur, Hakim; Sukarni, Sukarni (Asian Research Publishing Network (ARPN), 2024)
Coconut shell waste is underutilized due to the high demand for coconut in Indonesia. To maximize the use value of the material, coconut shells are converted into biomass energy, specifically charcoal briquettes. Due to the rapid advancement of technology today, it is necessary to use equipment that can run automatically to increase productivity, reduce production time, and lower production costs. This research was conducted to make an automatic cutting tool based on an Arduino microcontroller. The first process identified with literature studies related to automatic briquette cutting tools. The second process is conceptualised by assessing several design variants, then the highest value is taken. The third process is designing by making detailed drawings per component. The fourth process of completing the design by assembling all the components that have been made, and then testing the Arduino-based automatic cutting tool. The results obtained by the automatic cutting tool produce a cutting consistency of 77.5% and produce a residue of 22.5%. From the test data, the Arduino-based automatic cutting tool can work more effectively and efficiently to increase production capacity.